Characterization of body biometrics during growth of elite Santa Ines sheep - Milton Rezende Teixeira Neto; Jurandir Ferreira da Cruz; Carlos Henrique Mendes Malhado; Paulo Luiz Souza Carneiro; Rita de Cássia Santos Nunes; Luiz Miranda Souza; Luiz Eduardo Barreto de Souza (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to characterize body biometrics of Santa Ines sheep during growth. Data from 4,038 animals, males and females, with ages from four to 36 months, from different herds participating in the National Agricultural Fair in Bahia from 2003 to 2008 were used. The characteristics evaluated were: body weight, average daily gain, body length, thoracic circumference, anterior height and posterior height. The mean values found were compared by the Student-Newman-Keuls test. All characteristics studied showed gradual change with aging, and it is worth-noting that age had positive effect on body weight, body length, thoracic circumference, anterior height and posterior height and negative effect on average daily gain. Average daily gain was reduced by 68.5% from four to 36 months of age, while the mean improvements observed in both sexes in this age range, for body weight, body length, thoracic circumference, anterior height and posterior height were 137.8%, 23.5%, 43.2%, 19.3% and 19.6%, respectively. However, the increments for body weight, body length and thoracic circumference were higher until 12 months of age, when an increase of 72.7%, 14.6% and 24.8% in their respective characteristics was verified. For anterior height and posterior height, the greatest increase occurred up to eight months of age with improvement of 8.4% for both measures. Santa Ines sheep have different growth rates for body measurements; whereas growth in posterior height stabilizes earlier, the thoracic circumference, along with body weight, remains growing for longer time.